Cyanobacterial harmful bloom lipopolysaccharides: pro-inflammatory effects on epithelial and immune cells in vitro - Skočková, V; Raptová, P; Pospíchalová, K; Sovadinová, I; Sychrová, E; Smutná, M; Hilscherová, K; Babica, P; Šindlerová, L (Archives of toxicology, 2024)
Cyanobacterial harmful blooms (CyanoHABs) pose a global ecological problem, and their lipopolysaccharides (LPS) are among the bioactive compounds they release. Previous studies on CyanoHAB-LPS from single cyanobacterial species have shown varying bioactivities in different in vitro cell models. In this study, we isolated LPS from 19 CyanoHAB samples collected at 18 water bodies in the Czech Republic over two consecutive seasons. The proportions of cyanobacteria, Gram-negative bacteria (G-), and other bacteria in the biomass were determined by qPCR, while the cyanobacterial genera were identified using light microscopy. In vitro models of keratinocytes (HaCaT), the intestinal epithelium (co-culture of differentiated Caco-2 cells and peripheral blood mononuclear cells - PBMC), and PBMC alone were treated with isolated LPS at concentrations of 50, 100, and 1 µg/ml, respectively. The endotoxin activities of these concentrations were within the range measured in the aquatic environment. Approximately 85-90% of the samples displayed biological activity. However, the potency of individual LPS effects and response patterns varied across the different in vitro models. Furthermore, the observed activities did not exhibit a clear correlation with the taxonomic composition of the phytoplankton community, the relative share of microbial groups in the biomass, endotoxin activity of the LPS, or LPS migration and staining pattern in SDS-PAGE. These findings suggest that the effects of CyanoHAB-LPS depend on the specific composition and abundance of various LPS structures within the complex environmental sample and their interactions with cellular receptors.
Keywords: Caco-2 Cells; Inflammation; Keratinocytes; Lipopolysaccharide; sinice; lidé; Caco-2 buňky; škodlivý vodní květ; Lipopolysaccharides; leukocyty mononukleární; Cyanobacteria; Harmful Algal Bloom; Humans; lipopolysacharidy; Immune cells; Cyanobacterial harmful blooms; Biomass; Enterocytes; Leukocytes, Mononuclear; biomasa